South-South Migration and Remittances - Ratha, Dilip; Shaw, William (Washington, DC: World Bank, 2012)
South-South Migration and Remittances reports on preliminary results from an ongoing effort to improve data on bilateral migration stocks. It sets out some working hypotheses on the determinants and socioeconomic implications of South-South migration. Contrary to popular perception that migration is mostly a South-North phenomenon, South-South migration is large. Available data from national censuses suggest that nearly half of the migrants from developing countries reside in other developing countries. Almost 80 percent of South-South migration takes place between countries with contiguous borders. Estimates of South-South remittances range from 9 to 30 percent of developing countries' remittance receipts in 2005. Although the impact of South-South migration on the income of migrants and natives is smaller than for South-North migration, small increases in income can have substantial welfare implications for the poor. The costs of South-South remittances are even higher than those of North-South remittances. These findings suggest that policymakers should pay attention to the complex challenges that developing countries face not only as countries of origin, but also as countries of destination.